2022
DOI: 10.1177/25151274221091698
|View full text |Cite
|
Sign up to set email alerts
|

Adopting Entrepreneurship Education—TeachersProfessional Development

Abstract: This study explores teachers’ professional development in entrepreneurship education (EE). It examines empirically the change in teachers’ EE practices among Finnish teachers in 2011–2017. Overall, the quantitative analysis reveals that entrepreneurship education practices are increasing, albeit unevenly. Three groups of teachers, EE experimenters, EE critics, and EE selectors show different profiles in their use of EE practices. Furthermore, these groups seem to represent different stages of EE professionaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
(236 reference statements)
0
3
0
Order By: Relevance
“…Entrepreneurship education, which has been on the agenda worldwide in recent years, is aimed to increase the entrepreneurial characteristics of students by being included in education programs, especially in European countries (European Commission, 2016). Schools specialize in entrepreneurship education as teachers professionalize in entrepreneurship education (Oksanen et al, 2022). Teachers' lack of knowledge about the concept of entrepreneurship and inadequate ideas about the purpose, method, practices, and results of entrepreneurship education are one of the important situations encountered in entrepreneurship education program implementations carried out in this context (Sommarström et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Entrepreneurship education, which has been on the agenda worldwide in recent years, is aimed to increase the entrepreneurial characteristics of students by being included in education programs, especially in European countries (European Commission, 2016). Schools specialize in entrepreneurship education as teachers professionalize in entrepreneurship education (Oksanen et al, 2022). Teachers' lack of knowledge about the concept of entrepreneurship and inadequate ideas about the purpose, method, practices, and results of entrepreneurship education are one of the important situations encountered in entrepreneurship education program implementations carried out in this context (Sommarström et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Teachers' lack of knowledge about the concept of entrepreneurship and inadequate ideas about the purpose, method, practices, and results of entrepreneurship education are one of the important situations encountered in entrepreneurship education program implementations carried out in this context (Sommarström et al, 2017). Considering that teacher quality is one of the factors affecting student quality (Antony & Elangkumaran, 2020), it is necessary to examine in depth the factors that affect teachers' entrepreneurship education and their entrepreneurship (Oksanen et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be realized by training them to become entrepreneurs when they are still teacher candidates. The results showed that there was a positive and significant influence between entrepreneurial skills with professional attitudes and self-efficacy [2,4,5].…”
Section: Introductionmentioning
confidence: 96%